Practical dam analysis - Herzog, Max, Dr. techn (Thomas Telford, 1999)
With 26 fully-worked examples of dams around the world, this book presents simple approximate methods of analysing embankment, gravity and arch dams for design studies preliminary designs and estimates of quantities.